Classroom contexts for learning at primary and secondary school: Class size, groupings, interactions and special educational needs. (9th July 2018) - Blatchford, Peter; Webster, Rob
Abstract : The inclusion of pupils with special educational needs and disabilities (SEND) in mainstream schools can result in difficult decisions regarding classroom organisation and management. The premise of this article is that these are likely to be affected by the classroom context, specifically the number of pupils in the class, the size and composition of groups and classes, and the presence of additional adults, but that there is very little systematic information on these features. A systematic observation study was conducted involving 48 pupils at Year 5 (9–10 years) and 49 pupils at Year 9 (13–14 years) with Statements of SEND, along with 115 comparison pupils at Year 5 and 112 at Year 9 who were typically developing. There were nearly 70, 000 observations (data points) in total. Results showed that pupils at Year 5 with SEN were being taught in larger classes than at Year 9, and that, compared with typically developing pupils, they were much more likely to be separately taught in small, low‐attaining groups at Year 5 and small, low‐attaining classes (sets) at secondary. The study raises worrying questions about the appropriateness of classroom contexts for pupils with SEND and the heavy reliance on teaching assistants.